PENERAPAN TEKNIK BRAINSTORMING MELALUI GAMBAR UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MENULIS TEKS DESKRIPTIF - Siti Juliani; Sary Sukawati; Teti Sobari (IKIP Siliwangi, 2020)
This research is motivated by the use of learning methods that are not sometimes in accordance with the conditions and abilities of study. This study aimed to determine the effect of brainstorming technique through images to improve students’ ability to write descriptive texts. This research was condacted at one vocational school in Bandung the sample as 30 students. This research used quantitative method in collaborated with pre-experimental designs. The data in this study were collected by using writing test; pre-test and post-test. The research using statistical analysis for analysis the data. Test result was analyse to know whether there was significant difference in learners writing ability after the teacher used brainstorming technique in teaching writing descriptive text. Based on data analysis, it was discovered that the learners writing ability had improved. The improvement was in different criteria and from the hypothesis testing result, it was tobserved = 11.4118 and tcritical = 2.0452 thus, there was significan difference in learners’ writing ability after the teacher used brainstorming techniquein teaching writing skill of deskrptive text.. This study result is expected to give contributions and new perpective for teacher in teaching writing skill of descriptive text using brainstorming technique in improving learners’ writing skill.